Kajian Hukum Islam Terhadap Akad Kartu Kredit Hasanah Card Pada Bank Bni Syariah - Uswah, Intan Viana Zahrotun Nurul, Mutimatun Ni'ami, S.H., M.Hum (2016)
The continued development of the times it develops the technology sistem in the world, especially regarding the financial transaction sistem. The more widespread development of the banking world is a lot of variety of products that were returned by the bank agencies, among others, that the credit card. In this study, described the agreement on the credit card sistem hasanah card at BNI Sharia. The first is about the kinds of contract applied by BNI Sharia banks on credit card product, this name is hasanah credit card. Where there are 3 covenants applied by BNI Sharia products about hasanah credit card. The first (1) Ijarah, (2) kafalah contract, (3) the contract qard. The second is the view of Islamic law on the application of Islamic credit card agreement hasanah card by bank BNI sharia. That is where it is the whole process of contract committed by the bank BNI sharia law is in conformity with the teachings of Islam.